The Effects of Vitamin D and Marine Omega‐3 Fatty Acid Supplementation on Chronic Knee Pain in Older US Adults: Results From a Randomized Trial. Issue 11 (3rd October 2020) - MacFarlane, Lindsey A.; Cook, Nancy R.; Kim, Eunjung; Lee, I‐Min; Iversen, Maura D.; Gordon, David; Buring, Julie E.; Katz, Jeffrey N.; Manson, JoAnn E.; Costenbader, Karen H.
Abstract : Objective: Knee pain from osteoarthritis is frequent in the adult population. Prior trials have had conflicting results concerning the therapeutic effects of vitamin D on knee pain, and few trials have investigated marine Omega‐3 fatty acids (n‐3 FA). Methods: In the double‐blind, placebo‐controlled Vitamin D and Omega‐3 Trial (VITAL), 25, 871 US adults were randomized in a 2‐by‐2 factorial design to receive vitamin D or n‐3 FA. We identified a subgroup with chronic knee pain prior to randomization and assessed knee pain at baseline and annually during follow‐up using the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) (graded on a 0–100 scale, where 100 indicates worst symptoms). Repeated measures modeling was used to test the effect of randomized treatment on WOMAC pain scores over follow‐up after adjustment for age and sex. Analyses were repeated for WOMAC function and stiffness. Results: This study included 1, 398 participants who returned at least one knee pain questionnaire. The mean age was 67.7 years, 66% were women, and the mean ± SD WOMAC pain score was 37 ± 19. The mean ± SD follow‐up time was 5.3 ± 0.7 years. WOMAC pain did not differ between the active vitamin D group and the vitamin D placebo group or between the active n‐3 FA group and the n‐3 FA placebo group at any time point during follow‐up. Linear time‐by‐treatment interactions were not significant for either treatment (vitamin D, P = 0.41; n‐3 FA, P = 0.77). Vitamin D and n‐3 FA supplementation did not significantly affect WOMAC function or stiffness scores over time. Conclusion: Our findings indicate that vitamin D and n‐3 FA supplementation for a mean of 5.3 years does not reduce knee pain or improve function or stiffness in a large sample of US adults with chronic knee pain.